2007
DOI: 10.1080/10934520701418474
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of polycyclic aromatic hydrocarbons in surface soils and water from the vicinity of Agbabu bitumen field of Southwestern Nigeria

Abstract: Water and soil samples from the vicinity of Agbabu bitumen field of Southwestern Nigeria, were analyzed qualitatively and quantitatively for 10 parent polycyclic aromatic hydrocarbons (PAHs) using gas chromatography coupled by flame ionization detector (GC-FID), in order to gather information on the degree of contamination by bitumen exploration and processing in this area. The total concentrations of 10 PAHs varied from 11.2 to 341.5 microg L(- 1) in water and from 101.5 to 209.7 ng g(- 1) dry weight in soils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 30 publications
2
20
2
Order By: Relevance
“…The levels of PAHs in this study were higher than the values reported in studies around the world. This result is a re-affirmation of other studies in Nigeria that showed occurrence of PAHs in most potable water sources [34,45,46]. Therefore regular checks and control measures should be intensified to remediate the overwhelming effects for future generations to come.…”
Section: Evaluation Of Polycyclic Aromatic Hydrocarbons In Water Fromsupporting
confidence: 67%
See 1 more Smart Citation
“…The levels of PAHs in this study were higher than the values reported in studies around the world. This result is a re-affirmation of other studies in Nigeria that showed occurrence of PAHs in most potable water sources [34,45,46]. Therefore regular checks and control measures should be intensified to remediate the overwhelming effects for future generations to come.…”
Section: Evaluation Of Polycyclic Aromatic Hydrocarbons In Water Fromsupporting
confidence: 67%
“…Adeboyejo et al [45] Previous studies -water samples of Lagos lagoon ND -3.73(µg/L) ND -0.00373 (ng/µL) Present study was relatively much higher being about 1500 times higher for the control and 10 5 times for the catchment samples. Olajire et al [46] Water samples -Agbabu bitumen field, South-western, Nigeria Present study was relatively much higher being about 10 orders for the control and 10 3 orders for the catchment samples. European Community [41] 0.01 µg/L for BaP (a strongly carcinogenic PAHs) Present study is > by over 100 orders, which far exceeded EU regulatory limit for BaP.…”
Section: Evaluation Of Polycyclic Aromatic Hydrocarbons In Water Frommentioning
confidence: 99%
“…The exploitation and exploration of the Nigerian natural bitumen deposits can best be described to be at the planning stage. Previous studies on the Nigerian bitumen were concentrated on geological surveying of the deposits and the composition and engineering properties ofthe bitumen (Adegoke et al, 1980;Sonibare et al, 2003;Olajire et al, 2007;Adebiyi and Asubiojo, 2008;Oloke et al, 2009). Till date, there is little information regarding the biodegradability of Nigerian natural bitumen despite its potential as environmental pollutant.…”
Section: Microbial J 1 (4): 139-148 2011mentioning
confidence: 99%
“…Soil or water contamination originates mainly from PAH emissions to the atmospheres, which reach the soil or water bodies via precipitation. 3 Since these contaminated soil and water represent a longterm source of bitumen exposure to the indigenous people, it is imperative to characterize the toxicity of this compound in order to access its potential health risks. The probable reserve of bitumen and heavy oil in the entire Nigerian belt is about 120 Â 4 km, spreading along the bitumen belt encompassing Lagos, Ogun, Ondo and Edo States.…”
Section: Introductionmentioning
confidence: 99%